Michelangelo - Langley, Andrew (Chicago : Raintree, 2003)
Examines the life and accomplishments of sixteenth-century Italian sculptor and painter Michelangelo, and includes illustrations and photographs of his work.
A biography of the famous Renaissance artist and architect.
Includes bibliographical references (p. 31) and index.
Horn Book.
Catholic Library World.
5.1
3-6
Keywords: Michelangelo Buonarroti, -- 1475-1564 -- Juvenile literature; Michelangelo Buonarroti, -- 1475-1564.; Michelangelo Buonarroti, -- 1475-1564.; Artists -- Italy -- Biography -- Juvenile literature; Artists; Artists -- Italy -- Biography; Artists